Atmospheric plastics- a potential airborne fomite with an emerging climate signature - Renjith VishnuRadhan; Divya David Thresyamma; T I Eldho; Jacky Bhagat (Elsevier, 2021)
Plastic particles have become ubiquitous in various environmental compartments, with the atmosphere being the least explored of these. Furthermore, the way atmospheric plastics affect terrestrial biological systems has not been evaluated to the same extent as for aquatic ecosystems. Plastics are even found in human lungs, and hence their adverse effects on the respiratory system are one of the many purported human health impacts. In this review, we discuss the ability of suspended atmospheric plastics to act as a potential fomite for microbes in addition to their emerging influence on climatic activity. Atmospheric plastics can interact with solar radiation, produce greenhouse gases, and influence the carbon cycle, thereby becoming a prominent factor affecting climate change processes. Microbe-laden bioaerosols can adhere to plastic particles enabling long-distance travel and directly making way to the airway and lungs. The efficiency of these pathways in spreading microbial or viral infections can be examined once sufficient data regarding the spatial dynamics of any airborne pathogen transmission is available. Astute investigations on atmospheric plastics and their complex interactions in the earth system are needed.